Transient Ca2+ entry by plasmalogen-mediated activation of receptor potential cation channel promotes AMPK activity - Honsho, Masanori; Mawatari, Shiro; Fujino, Takehiko (Frontiers in Molecular Biosciences, 2022)
Ethanolamine-containing alkenyl ether glycerophospholipids, plasmalogens, are major cell membrane components of mammalian cells that activate membrane protein receptors such as ion transporters and G-protein coupled receptors. However, the mechanism by which plasmalogens modulate receptor function is unknown. Here, we found that exogenously added plasmalogens activate transient receptor potential cation channel subfamily C member 4 (TRPC4) to increase Ca2+ influx, followed by calcium/calmodulin-dependent protein kinase 2-mediated phosphorylation of AMP-activated protein kinase (AMPK). Upon topical application of plasmalogens to the skin of mice, AMPK activation was observed in TRPC4-expressing hair bulbs and hair follicles. Here, TRPC4 was co-localized with the leucine-rich repeat containing G protein-coupled receptor 5, a marker of hair-follicle stem cells, leading to hair growth. Collectively, this study indicates that plasmalogens could function as gate openers for TRPC4, which is widely expressed in human tissues, followed by AMPK activation and downstream signaling, thereby leading to hair growth acceleration in mice.